Crafting gongs in two Ifugao communities in Northern Philippines - Montano, Lilymae Franco (2008)
This thesis presents a study of the flat gong tradition of the municipalities of Hingyon and Banaue in the province of Ifugao in the Cordillera Region of Northern Philippines.
"April 2008."
Thesis (M. Music) -- University of the Philippines Diliman.
Keywords: Musical instruments -- Construction -- Philippines; Music and society -- Philippines; Gong -- Philippines -- Cordillera Region -- Banaue (Ifugao); Gong -- Philippines -- Cordillera Region -- Hingyon (Ifugao)